2010
DOI: 10.1134/s1070428010060126
|View full text |Cite
|
Sign up to set email alerts
|

Amination of 5-hydroxy-1,4-naphthoquinone in the presence of copper acetate

Abstract: The reaction of 5-hydroxy-1,4-naphthoquinone with butylamine in the presence of copper(II) acetate monohydrate on heating resulted in the formation of a mixture of regioisomeric 2,6-and 2,8-bis(butylamino)-5-hydroxy-1,4-naphthoquinones.Naphthoquinone derivatives having hydroxy and amino groups attract interest as potential biologically active substances [1], dyes [2], and organic materials for nonlinear optics [3]. It is known that 5-hydroxy-1,4-naphthoquinone (I, juglone) reacts with amines only at the quinoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The reaction produced 13a in 13.9% as an orange red solid; mp 154.6–155.4 °C (lit. [41] 156–157 °C). 1 H-NMR (500 MHz, CDCl 3 ) δ H 0.96 (t, J = 7.4 Hz, 3H, CH 3 ), 1.43 (p, J = 7.5 Hz, 2H, H-2′), 1.67 (p, J = 7.5 Hz, 2H, H-3′), 3.17 (q, J = 6.9 Hz, 2H, H-1′), 5.61 (s, 1H, H-3), 6.04 (s, 1H, -NH), 7.22 (dd, J = 0.8, 8.3 Hz, 1H, H-8), 7.44 (t, J = 8.0 Hz, 1H, H-7), 7.56 (dd, 1H, J = 0.8, 7.6 Hz, H-6), 13.08 (s, 1H, 5-OH); 13 C-NMR (125 MHz, CDCl 3 ) δ C 13.90 (CH 3 ), 20.40 (C-2′), 30.43 (C-3′), 42.63 (C-1′), 99.81 (C-3), 115.19 (C-9), 119.25 (C-6), 126.18 (C-8), 130.70 (C-10), 134.05 (C-7), 148.90 (C-2), 161.33 (C-5), 181.41 (C=O), 189.14 (C=O); LC-MS (ESI + , m / z ) calculated for C 14 H 15 NO 3 : 245.11, found for 268.24 [M + Na] + ; HRMS-ESI: m / z calculated for C 14 H 16 O 3 N: 246.1125 [M + H] + , found for 246.1120.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction produced 13a in 13.9% as an orange red solid; mp 154.6–155.4 °C (lit. [41] 156–157 °C). 1 H-NMR (500 MHz, CDCl 3 ) δ H 0.96 (t, J = 7.4 Hz, 3H, CH 3 ), 1.43 (p, J = 7.5 Hz, 2H, H-2′), 1.67 (p, J = 7.5 Hz, 2H, H-3′), 3.17 (q, J = 6.9 Hz, 2H, H-1′), 5.61 (s, 1H, H-3), 6.04 (s, 1H, -NH), 7.22 (dd, J = 0.8, 8.3 Hz, 1H, H-8), 7.44 (t, J = 8.0 Hz, 1H, H-7), 7.56 (dd, 1H, J = 0.8, 7.6 Hz, H-6), 13.08 (s, 1H, 5-OH); 13 C-NMR (125 MHz, CDCl 3 ) δ C 13.90 (CH 3 ), 20.40 (C-2′), 30.43 (C-3′), 42.63 (C-1′), 99.81 (C-3), 115.19 (C-9), 119.25 (C-6), 126.18 (C-8), 130.70 (C-10), 134.05 (C-7), 148.90 (C-2), 161.33 (C-5), 181.41 (C=O), 189.14 (C=O); LC-MS (ESI + , m / z ) calculated for C 14 H 15 NO 3 : 245.11, found for 268.24 [M + Na] + ; HRMS-ESI: m / z calculated for C 14 H 16 O 3 N: 246.1125 [M + H] + , found for 246.1120.…”
Section: Methodsmentioning
confidence: 99%
“…The reactivity of amine vs quinone was also studied, and it was observed that amines have relatively weak basicity compared to Lewis acid quinone, leading to the failure of the amination of quinones. Inspired by these results, Ektova and co‐workers explored the regioselectivity for amination of 5‐hydroxy‐1,4‐naphthoquinone, and they further studied the crystal packing of these molecules [120b] . From structural analysis, they found that extended π‐conjugation system with intramolecular charge transfer from the hydroxy and amino groups to the carbonyl groups and also substantial intra and intermolecular H‐bonding enhancing the stacked molecular bands, which could be responsible for their non‐linear optical properties.…”
Section: Direct Functionalization Of Quinonesmentioning
confidence: 99%
“…Three major synthetic strategies have been used for synthesizing 2-amino-1,4-naphthoquinone until now, one of which involves the nucleophilic displacement of the halo group in quinone with amines, ,,, while the second involves a direct 1,4-addition of amines to the quinones, ,, and the third strategy utilized metal catalyzed C–H functionalization of 1,4-naphthoquinone with an amine. ,,, However, the developed methodologies require strong acidic conditions, high temperature, metal catalysts, stoichiometric quantities of oxidant, or a strenuous process and also provide lower yields (Scheme ). ,,, …”
Section: Introductionmentioning
confidence: 99%